Parler du moyen âge?: - Morais, Ana Paiva (2009)
This paper focuses on aspects of medieval literature which draw on image studies. The aim is to review some of those aspects starting with the works of historians, such as Jacques Le Goff and Georges Duby, which have inspired medieval studies from the standpoint of what is nowadays known as “historical anthropology”, as well as the system of anthropological structures of the imaginary set up by Gilbert Durand from which a vast and rich criticism of medieval imaginary has developed. The suggestions of Jean-Claude Schmitt opened the way to further works which proved to be as fruitful: taking a strong interest in the “body of images” (“corps des images”), Schmitt has at times turned to art history in search for his materials of study from which he has drawn some of his most suggestive insights on medieval history and culture. The rhetoric turn, specifically, the new interest in “images of thought” springing from Mary Carruthers’ and Jan Ziolkowski’s recent works has led medieval scholars to focus on the text as an art (téchné or “craft of thought”).